Anthropology, Democracy, and Authoritarianism: Reflections from Brazil and the Philippines - Gonçalves, João Felipe (Archīum Ateneo, 2023)
This article examines the challenges that the right-wing populist governments in Brazil and the Philippines pose to anthropological practices as a way of discussing the responses and responsibilities of anthropologists vis-à-vis situations of growing authoritarianism across the globe. It explores the importance of public and political engagement for the national anthropologies that have developed in Brazil and the Philippines and stresses their complex relationship to recent dictatorial and democratic regimes. It discusses the threats that Jair Bolsonaro’s and Rodrigo Duterte’s governments have brought to the discipline and to the oppressed and marginalized subjects that anthropologists in those countries have typically studied and allied themselves with, as well as the reaction of anthropologists to such threats. Showing that the current Brazilian and Philippine governments combine economic and social neoliberalism with deeply illiberal political practices, the article proposes a fundamental distinction between liberal democracy and neoliberalism to argue that liberal democratic institutions and practices are fundamental conditions for the possibility of a politically engaged and publicly relevant anthropology.